الرؤوى التي عبرها النبي صلى الله عليه وسلم جمعا ودراسة - بايزيد, نور شمس الدين; خالدي, عبد الودود (University of Eloued-جامعة الوادي, 2022)
" الحمد لله وحده والصلاة والسلام على من لا نبي بعده ثم أما بعد: فمن فضل الله علينا أن جعلنا من أمة نبينا محمد صلى الله عليه وسلم وفطر قلوبنا على محبته واتباع سنته المطهرة، ومن سنته تلكم الرؤى التي رءاها صلى الله عليه وسلم أو رآها أصحابه رضوان الله عليهم وفسرها لهم، مما كان يعرض لهم في المنام فيستشيرونه فيها فيوضحها ويفسرها لهم، ونظرا لأهمية هذا الموضوع إذ يبني عليه كثير من الناس حياته تفاؤلا وتشاؤما فقد اخترنا هذا البحث مبينين فيه المسلك النبوي في تفسير تلك الرؤى وجعها ممن طرق التعلم التي تقوم سلوكات الناس وكذا بيان عظمته صلى الله عليه وسلم وصدق نبوته، ثم ختمنا بخاتمة متبوعة ببعض النتائج. ونسأل الله تعالى أن ينفع بهذا البحث ويجعله خالصا لوجهه الكريم وصلى الله وسلم على نبينا محمد وعلى آله وصحبه ومن سار على هديه واقتفى أثره لإلى يوم الدين وسلم تسليما."" Praise be to Allah, and prayers and peace be upon the one after whom there is no prophet. Then as for what follows: It is God’s grace upon us that He made us from the nation of our Prophet Muhammad, may God bless him and grant him peace, and open our hearts to love for him and to follow his purified Sunnah, and from his Sunnah are those visions that saw him, may God’s prayers and peace be upon him, or that his companions saw the pleasure of. May God bless them and explain it to them, from what was presented to them in a dream, so they consult him in it, and he clarifies it and explains it to them, and given the importance of this topic as many people build on it their lives with optimism and pessimism, we have chosen this research showing the prophetic path in the interpretation of those visions and their pain from the ways of learning that are based on people’s behavior As well as the statement of his greatness, may God’s prayers and peace be upon him, and the truthfulness of his prophet hood, then we concluded with a conclusion followed by some results. And we ask God Almighty to benefit from this research and make it purely for his honorable face, and may God’s prayers and peace be upon our Prophet Muhammad, his family and companions, and those who followed his guidance and traced his trail to the Day of Judgment, and peace be upon him."
مذكرة ماستر
Keywords: الرؤى -التعبير -التأويل; visions - expression - interpretation